The Importance of Performance Appraisal Management and Job Promotion in Shaping Employee Work Productivity - Fakhita Hannan Nasutioin; Mu’thial Abadi; Ritha F. Dalimunthe; Prihatin Lmbanraja (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Abstract, Performance appraisal and promotion management are crucial elements in human resource management aimed at increasing productivity and creating a competitive work culture. Performance appraisal enables objective evaluation of employee contributions, identifying training needs, and building transparent career development paths. Meritocratic-based promotion not only encourages employee motivation and loyalty, but also minimizes the potential for internal conflict and the risk of bias. The results of the study indicate that an effective performance appraisal system contributes to talent retention, job satisfaction, and innovation in the organization. With a structured and development-oriented approach, companies can ensure sustainable productivity and strong leadership.